2022
DOI: 10.1155/2022/9224203
|View full text |Cite|
|
Sign up to set email alerts
|

Research on Face Recognition Algorithm Based on Image Processing

Abstract: While network technology is convenient for our daily life, the problems that are exposed are also endless. The most important thing for everyone is information security. In order to improve the security level of network information and identify and detect faces, the method used in this paper has improved compared with the traditional AdaBoost method and skin color method. AdaBoost detection is performed on the image, which reduces the probability of false detection. The experiment compares the experimental res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…For this reason, researchers have developed the multifeature decision fusion for the problem of face recognition [18][19][20]. Judging from the reported results, the joint application of multiple features can effectively improve the performance of face recognition, which has advantages over a single category of features [21][22][23][24][25]. However, the current multifeature fusion method has certain shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, researchers have developed the multifeature decision fusion for the problem of face recognition [18][19][20]. Judging from the reported results, the joint application of multiple features can effectively improve the performance of face recognition, which has advantages over a single category of features [21][22][23][24][25]. However, the current multifeature fusion method has certain shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%